A Breakthrough in Anomaly Detection using Variational Auto-encoders and Enhanced Clustering Technique Using Elevating Spam Review Detection - S, Sripathi; P M, Shanthi (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research presents pioneering techniques aimed at revolutionizing the field of anomaly detection, with a specific focus on the critical task of identifying spam reviews within textual data. In a world where user-generated content is prolific and indispensable, the need for robust spam review detection mechanisms is more pressing than ever. Our approach represents a significant leap forward in addressing this challenge. At the core of our methodology are two novel techniques: Deep Convolutional variational Auto-encoders (DC-VAEs) for feature extraction and Hierarchical Density-Based Clustering (H-DBSCAN) for enhanced clustering. DC-VAEs, implemented using the PyTorch framework, enable the extraction of intricate and context-aware features from textual data. By harnessing the inherent power of convolutional neural networks, DC-VAEs excel in capturing subtle patterns, nuances, and anomalies that often elude traditional methods. Complementing the feature extraction process of DC-VAEs is our innovative use of H-DBSCAN, implemented in Python, which offers a robust hierarchical clustering framework. This method excels in segregating legitimate reviews from spam, exhibiting a high degree of accuracy. The hierarchical nature of H-DBSCAN enables the identification of clusters at multiple granularity levels, allowing for a nuanced understanding of the data distribution and anomaly patterns. Extensive experimentation across diverse real-world datasets validates the effectiveness of our approach. Notably, our techniques consistently outperform conventional methods, yielding a groundbreaking achievement in the realm of spam review detection. This research signifies a significant advancement in the state-of-the-art for anomaly detection within textual data. Moreover, the implications of our findings extend beyond spam review identification. The combination of DC-VAEs and H-DBSCAN has demonstrated its potential as a formidable tool in various domains where precise anomaly detection holds paramount importance. This includes fields such as fraud detection, cybersecurity, and quality control, where our techniques can be adapted to uncover hidden anomalies and enhance decision-making processes. Thus, our research not only contributes substantially to the enhancement of spam review identification but also opens up new avenues for advancing anomaly detection techniques in diverse applications.